Conceptions of Chinese democracy reading Sun Yat-Sen, Chiang Kai-Shek and Chiang Ching-Kuo - Lorenzo, David J., 1961- (Johns Hopkins University Press, 2013)
Conceptions of Chinese Democracy provides a coherent and critical introduction to the democratic thought of three fathers of modern Taiwan--Sun Yat-sen, Chiang Kai-shek, and Chiang Ching-kuo--in a way that is accessible and grounded in broader traditions of political theory. David J. Lorenzo's comparative study allows the reader to understand the leaders' democratic conceptions and highlights important contradictions, strengths, and weaknesses that are central to any discussion of Chinese culture and democratic theory. Lorenzo further considers the influence of their writings on political theorists, democracy advocates, and activists on mainland China. Students of political science and theory, democratization, and Chinese culture and history will benefit from the book's substantive discussions of democracy, and scholars and specialists will appreciate the larger arguments about the influence of these ideas and their transmission through time.